Kontribusi Etika dan Tanggung Jawab Bisnis (CSR) dalam Keberlangsungan Perusahaan Manufaktur Victor - Triannanda Siahaan; Jonatan Basrianto; Muzakki Ahmad Ath Thoriq; Ester Carolina Simanihuruk; Dionisius Sihombing; Fadli Agus Triansyah (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study analyzes the contribution of business ethics and corporate social responsibility (CSR) to business sustainability at Victor Manufacturing Company. This research used a case study approach with qualitative methods. Data were collected through semi-structured interviews, observations, and documentation to understand business ethics practices and CSR implementation and their impact on the company's economic, social, and environmental aspects. The results show that the company's implementation of business ethics focuses on quality service, integrity, and respect for customers. This has a positive impact on customer loyalty and harmonious relationships with business partners. The CSR program serves as a sustainability strategy that builds reciprocal relationships with the community and mitigates the negative impacts of operational activities. Obstacles identified included a lack of communication and differing perceptions between the company and consumers. Overall, business ethics and CSR have proven to play a significant role in strengthening Victor Manufacturing Company's reputation, trust, and sustainability amidst increasingly fierce market competition. Furthermore, this study emphasizes the crucial role of top management in instilling ethical values and social responsibility in the workplace. Leadership support is a key factor in ensuring policies and operational activities remain aligned with sustainability principles. Consistent implementation of business ethics and CSR not only enhances a company's positive image but also serves as a long-term investment in maintaining stability and competitive advantage. Corporate success in the modern era is no longer measured solely by economic profit, but also by the social and environmental contributions it makes to society.